Lizard's guest - Shannon, George, 1952-; Aruego, Jose; Dewey, Ariane (New York : Greenwillow Books, 2003)
While dancing around, Lizard accidentally steps on Skunk's toes and then promises to take care of lazy Skunk until his foot is healed.
Keywords: Lizards -- Fiction; Skunks -- Fiction; Honesty -- Fiction; Laziness -- Fiction